ANALISIS KEBIJAKAN PENDIDIKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU - Khatimah, Nur Husnul; Naro , Wahyuddin; Yuspiani , Yuspiani (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
There are still disparities in the quality of education in several regions in Indonesia, which shows a clear gap in educational services. The government's efforts to advance education in Indonesia through education equality programs have been implemented in various ways. One of the steps taken to improve and equalize the quality of education is through the implementation of a zoning system in the process of accepting new students. This zoning system is regulated in Minister of Education and Culture Regulation Number 14 of 2018. The zoning system is a form of effort to equalize education and aims to eliminate the image of superior schools that has spread widely in society. With this zoning system, it is hoped that all schools will have equal quality, and there will no longer be preferences for certain schools. However, this new policy cannot be separated from the potential for problems to arise, both in terms of school management and from the community, especially student parents as consumers of education. This research aims to analyze educational policies related to the zoning system in the process of admitting new students, using qualitative research methods with a document/text study approach.